Study of School Eye Survey Conducted in Rural Areas of Jalandhar (Punjab), India: An investigation into the prevalence of refractive errors and ocular morbidity among school children in a rural village (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In order to determine the prevalence of refractive errors and the pattern of ocular morbidityamong the school children of a rural village, the purpose of this study was to gather this information. Across-sectional study was conducted on children aged 4 to 15 years old in a rural village -Damurdarpur,Jalandhar( Punjab). The location of the study was in India. Every child was given a full eye exam, whichconsisted of retinoscopy, refraction under cycloplegia, and a measurement of the child's visual acuityusing Snellen's E chart. In addition to that, the anterior segment, the media, and the fundii were allexamined. Myopia was defined as a sphericalcylindrical equivalent refractive error of at least -0.50 D,and hypermetropia was defined as having a refractive error of +0.50 D or more . The survey involved theexamination of 220 eyes belonging to 110 children, the majority of whom were in the age range of 5 to 10years old. There were 85.40 percent of people who had a prevalence of uncorrected visual acuity of 66.